INCREASING STUDENTSâ READING COMPREHENSION OF RECOUNT TEXT BY USING STUDENT TEAM ACHIEVEMENT DIVISION (STAD) TECHNIQUE: A Classroom Action Research To The Second Year Students Of Madrasah Tsanawiyah YASTI Singkawang In Academic Year 2013/2014 - Samiaji, Bayu (West Kalimantan Scholars: Studies on English Language and Education, 2014)
This research is aimed to increase studentsâ reading comprehension of recount text to the second year students of MTs YASTI Singkawang. The method of this research was Classroom Action Research. The sample was 27 second year students of MTs YASTI Singkawang. The tools of collecting data were presented in observation checklist, field note, and individual test. The results showed that STAD technique could improve studentsâ reading comprehension on recount text by three cycles of CAR.